2023
DOI: 10.3390/microplastics2010007
|View full text |Cite
|
Sign up to set email alerts
|

May a Former Municipal Landfill Contaminate Groundwater in Microplastics? First Investigations from the “Prairie de Mauves Site” (Nantes, France)

Abstract: Municipal landfills receive a high amount of plastic waste and due to the occurring physical and biochemical degradation processes, could be significant sources of microplastics (MP). Evaluating the threat to groundwater through the transfer of MP via landfill leachates require more research. The former “Prairie de Mauves” landfill, operated from 1963 to 1987 by the municipality of Nantes (France), and located above the alluvial groundwater of the Loire River, represents a good candidate for such investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There appears to be a lack of specific guidelines in the literature for determining the optimal depth for sampling in a well or below the GW table. In some articles, the depth at which sampling was performed is not mentioned [109,110,113]. Selvam et al [2] state that sampling was carried out at a depth of 2-5 m. Samandra et al [108] report that sampling was performed at the mid-point of the screened interval of the boreholes.…”
Section: Challenges Associated With Sampling Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…There appears to be a lack of specific guidelines in the literature for determining the optimal depth for sampling in a well or below the GW table. In some articles, the depth at which sampling was performed is not mentioned [109,110,113]. Selvam et al [2] state that sampling was carried out at a depth of 2-5 m. Samandra et al [108] report that sampling was performed at the mid-point of the screened interval of the boreholes.…”
Section: Challenges Associated With Sampling Methodsmentioning
confidence: 99%
“…Recent studies have identified various MP contamination sources in GW, including septic tanks, landfills, sewage treatment plants, and agricultural areas [109,[113][114][115]. A significant correlation has been found between MP abundance in GW and the total concentration of antibiotics, proving that sewage treatment plants are a source of contamination [109].…”
Section: Occurrence Of Mps In Gwmentioning
confidence: 99%
See 3 more Smart Citations